The Influence of Financial Literacy, Financial Behavior, and Overconfidence on the Investment Decisions of Generation Z: College Students in Indonesia - Fatiyah, Rhatu Syelga; Adiputra, Danang (Dinasti Publisher, 2026)
This study aims to analyze the influence of financial literacy, financial behavior, and overconfidence on the investment decisions of Generation Z students in Indonesia. This study uses a quantitative approach with a survey method, utilizing a questionnaire distributed via Google Forms with a 5-point Likert scale. A sample of 294 students aged 18–25 years who have made investments was obtained. Data analysis techniques include descriptive statistics, data quality checks, classical assumption tests, and multiple linear regression analysis, including T-tests, F-tests, and coefficient of determination tests, using IBM SPSS version 22. The results indicate that financial literacy, financial behavior, and overconfidence have a positive and significant influence on the investment decisions of Generation Z students in Indonesia.